The Mycobacterial DNA Methyltransferase HsdM Decreases Intrinsic Isoniazid Susceptibility - Xinling Hu (MDPI AG, 2021)
Tuberculosis, caused by the pathogen Mycobacterium tuberculosis, is a serious infectious disease worldwide. Multidrug-resistant TB (MDR-TB) remains a global problem, and the understanding of this resistance is incomplete. Studies suggested that DNA methylation promotes bacterial adaptability to antibiotic treatment, but the role of mycobacterial HsdM in drug susceptibility has not been explored. Here, we constructed an inactivated Mycobacterium bovis (BCG) strain, ΔhsdM. ΔhsdM shows growth advantages over wild-type BCG under isoniazid treatment and hypoxia-induced stress. Using high-precision PacBio single-molecule real-time sequencing to compare the ΔhsdM and BCG methylomes, we identified 219 methylated HsdM substrates. Bioinformatics analysis showed that most HsdM-modified genes were enriched in respiration- and energy-related pathways. qPCR showed that HsdM-modified genes directly affected their own transcription, indicating an altered redox regulation. The use of the latent Wayne model revealed that ΔhsdM had growth advantages over wild-type BCG and that HsdM regulated trcR mRNA levels, which may be crucial in regulating transition from latency to reactivation. We found that HsdM regulated corresponding transcription levels via gene methylation; thus, altering the mycobacterial redox status and decreasing the bacterial susceptibility to isoniazid, which is closely correlated with the redox status. Our results provide valuable insight into DNA methylation on drug susceptibility.